Detection of enterotoxigenic Escherichia coli by colony hybridization with biotinylated enterotoxin probes. - Kirii, Y (J Clin Microbiol, 1987)
By using biotinylated enterotoxin DNA probes, a method to detect enterotoxigenic Escherichia coli by colony hybridization was developed. The treatment of colonies on nitrocellulose membrane filters with proteinase K and Triton X-100 was essential for obtaining the specific hybridization. A total of 200 E. coli strains isolated from travelers with diarrhea were tested for colony hybridization by using a probe encoding heat-labile toxin (LT) type h. All strains (86 of 86) that produced LT, but none of the non-LT producers, hybridized with 32P-labeled and biotinylated LT type h probes. A total of 36 strains chosen randomly from the 200 isolates were tested for colony hybridization by using heat-stable enterotoxin (ST) probes. All but two strains that hybridized with the 32P-labeled ST type Ia probe also hybridized with the biotinylated ST type Ia probe. All strains that hybridized with the 32P-labeled ST type Ib probe also hybridized with the biotinylated ST type Ib probe. Thus, almost all E. coli strains tested were judged to be the same by colony hybridization with biotinylated or 32P-labeled enterotoxin probes. These results demonstrate that the biotinylated enterotoxin probes are useful in the diagnosis of enterotoxigenic E. coli strains by colony hybridization. IMAGES: